2018
DOI: 10.3390/molecules23020406
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hexavalent Chromium and Detection of Chromate Reductase (ChrR) in Stenotrophomonas maltophilia

Abstract: An Gram negative strain of S. maltophilia, indigenous to environments contaminated by Cr(VI) and identified by biochemical methods and 16S rRNA gene analysis, reduced chromate by 100%, 98–99% and 92% at concentrations in the 10–70, 80–300, and 500 mg/L range, respectively at pH 7 and temperature 37 °C. Increasing concentrations of Cr(VI) in the medium lowered the growth rate but could not be directly correlated with the amount of Cr(VI) reduced. The strain also exhibited multiple resistance to antibiotics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 86 publications
4
43
0
1
Order By: Relevance
“…Biofilm requires a moist environment and constant supply of nutrient (Singh et al 2006). Many researchers showed the promising results of Cr(VI) reduction by biofilm as biofilm showed the high tolerance for the higher concentration of chromium and high hydraulic loading (Nancharaiah et al 2010;Vayenas, 2011;Tekerlekopoulou et al 2013;Baldiris et al 2018).…”
Section: Bioreactor Techniquesmentioning
confidence: 99%
“…Biofilm requires a moist environment and constant supply of nutrient (Singh et al 2006). Many researchers showed the promising results of Cr(VI) reduction by biofilm as biofilm showed the high tolerance for the higher concentration of chromium and high hydraulic loading (Nancharaiah et al 2010;Vayenas, 2011;Tekerlekopoulou et al 2013;Baldiris et al 2018).…”
Section: Bioreactor Techniquesmentioning
confidence: 99%
“…Chromate reductases have received recent attention and very few reports exist on their purification and characteristics of the purified enzymes. Generally, crude extracts of ChrRs have been characterized for their biochemical and physiochemical properties [18,42] . This is because their potential applications for bioremediation of contaminated environments require cost-effective procedures and purification to homogeneity is avoided.…”
Section: Structural and Genomic Features Of Chrrsmentioning
confidence: 99%
“…a stress factor such as Cr metal ions to tolerate the stress load and to perform their metabolic activities. Hexavalent Cr reduction was evaluated in crude cell-free extracts of Stenotrophomonas maltophilia and a protein of molecular weight about 25kDa was obtained in an SDS-PAGE gel with its band intensity corresponding to the concentrations of Cr 6+ in the culture medium [42] . The protein band could be the reductase enzyme that was responsible for chromate reduction, which was confirmed to be ChrR by in-silico studies.…”
Section: Structural and Genomic Features Of Chrrsmentioning
confidence: 99%
“…Ni nanoparticle encapsulated carbon nanotube was used as catalyst for the reduction chromium (VI) . Stenotrophomonasmultophilia‐reduced chromium (VI) was reported in the literature . In 2017, Shao et al reported the catalytic reduction of chromium (VI) using the AuPd@Pd catalyst system.…”
Section: Introductionmentioning
confidence: 99%
“…9 Stenotrophomonasmultophilia-reduced chromium (VI) was reported in the literature. 10 In 2017, Shao et al 11 reported the catalytic reduction of chromium (VI) using the AuPd@Pd catalyst system. The other catalyst systems like SrTiO 3 and Pd 12 were used for the reduction of chromium (VI).…”
Section: Introductionmentioning
confidence: 99%